Alison the art fairy - Meadows, Daisy (London : Orchard Books, 2016)
Alison the Art Fairy makes sure that all art classes are fun. But when Jack Frost steals her magical badge, everything starts to fall apart! Can Rachel and Kirsty help save the school art display.
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction